Exploring lived experiences with tooth loss among fully edentulous patients attending Makerere University Dental Hospital, Kampala, Uganda - David Nono; Godfrey Bagenda; Isaac Okullo; Charles Mugisha Rwenyonyi (BMC, 2024)
Abstract Background One of the most prevalent oral health issues affecting mankind is tooth loss. Besides extractions due to periodontal disease and caries, accidents and lack of dental knowledge can also result in tooth loss. Nevertheless, no known published studies have examined how edentulous patients in Uganda have lived with tooth loss. The objective of the present study was to investigate experiences of tooth loss among Ugandan edentulous patients attending Makerere University Dental Hospital. Methods This was a cross-sectional qualitative study using purposive recruitment of respondents. A total of 15 respondents were chosen from a variety of socio-economic groups. Qualitative data were collected using oral interviews in form of note taking and an audio-recorder. The data collected comprised the causes of tooth loss, the physical and psychological effects of losing teeth, the difficulties in managing oral hygiene when one is toothless, coping mechanisms, and supportive interventions after losing natural teeth. The collected data were transcribed and analyzed thematically using a software, Atlas Ti. The generated qualitative data were summarized as text, while demographic characteristics were presented in a table. Results Oral infections such as periodontal disease (which destroy tooth supporting tissues), tooth decay and trauma from accidents were reportedly the main causes of tooth loss. In case of tooth pain as a first symptom, most patients choose self-medication with over-the-counter drugs and home remedies. They only consult dental professionals when the condition deteriorates. Tooth loss was associated with problems of eating, facial aesthetics and low self-esteem. Conclusion The present study found that tooth loss was caused by periodontal disease, tooth decay and trauma from accidents. Loss of teeth was escalated by poor health seeking behavior. Tooth loss resulted in pain, eating difficulties, speech difficulties, poor facial appearance and consequently low self-esteem.